Dinámicas espaciales de la minería de oro y sus efectos sobre la pérdida de los bosques tropicales y afectaciones en los recursos hídricos, aplicando sensores remotos: caso de la cuenca alta del Río Napo, Amazonía, Ecuador. - Lucas Solis, Oscar Enrique (2021)
Gold mining (GM) impacts are devastating, including landscape change and deforestation, loss of ecosystem services and native species, contribution of carbon emission and sediment loads, reduced water quality, and soil and air contamination. The rapid increase in this activity across the Amazon basin, the scarcity of studies, the difficult detection of impacts and monitoring require integrated techniques that can assess the impact of GM on this important ecosystem. Google Earth Engine (GEE) is a useful tool for evaluating anthropic activities incidence on the dynamics of planetary coverage. Thus, this study seeks to use a remote sensing technique in GEE to assess land cover and land use changes dynamics and impacts derived from GM activity over a 6-year period in the Ecuadorian Amazon and to associate them with quality auxiliary data water and metal contamination in water and sediment to understand the degree of contamination and its risks to environmental health. GM doubled its extent from 0.15% (651 ha) to 0.30% (1317 ha) of the total study area, degrading mainly forested areas and leaving heterogeneous landscapes covered by grassy or bare soils. The combination of GM area change indicators with environmental quality data has made it possible to assess the mining activity impact in an integrative way in 9 GM sites, showing that sites with rapid increase of its extent and landscape degradation have a direct effect on metal contamination in water and physicochemical parameters, while places with lower increase have a higher occurrence of metals in sediments and a greater change in its location than in its extension.